Bone mineral density in children with acute lymphoblastic leukemia. Issue 5 (19th December 2017) - Inaba, Hiroto; Cao, Xueyuan; Han, Alice Q.; Panetta, John C.; Ness, Kirsten K.; Metzger, Monika L.; Rubnitz, Jeffrey E.; Ribeiro, Raul C.; Sandlund, John T.; Jeha, Sima; Cheng, Cheng; Pui, Ching‐Hon; et al.
Abstract : BACKGROUND: Children with acute lymphoblastic leukemia (ALL) can develop reduced bone mineral density (BMD). However, data from patients who received treatment on a frontline regimen without cranial irradiation are limited, and no genome‐wide analysis has been reported. METHODS: Lumbar BMD was evaluated by quantitative computed tomography at diagnosis, after 120 weeks of continuation therapy, and after 2 years off therapy in pediatric patients with ALL (ages 2‐18 years at diagnosis) who were treated on the St. Jude Total XV Protocol. Clinical, pharmacokinetic, and genetic risk factors associated with decreased BMD Z‐scores were evaluated. RESULTS: The median BMD Z‐score in 363 patients was 0.06 at diagnosis, declined to −1.08 at week 120, but partly recovered to −0.72 after 2 years off therapy; BMD in patients with low BMD Z‐scores at diagnosis remained low after therapy. Older age (≥10 years vs 2‐9.9 years at diagnosis; P < .001), a higher BMD Z‐score at diagnosis ( P = .001), and a greater area under the plasma drug concentration‐time curve for dexamethasone in weeks 7 and 8 of continuation therapy ( P = .001) were associated with a greater decrease in BMD Z‐score from diagnosis to week 120. Single‐nucleotide polymorphisms in 2 genes important in osteogenesis and bone mineralization ( COL11A1 [reference single‐nucleotide polymorphism rs2622849]; P = 2.39 × 10 −7 ] and NELL1 [rs11025915]; P = 4.07 × 10 −6 ]) were associated with a decreased BMD Z‐score. NELL1 ( P = .003) also was associated with a greater dexamethasone area under the plasma drug concentration‐time curve. CONCLUSIONS: BMD Z‐scores decreased during therapy, especially in patients who had clinical, pharmacokinetic, and genetic risk factors. Early recognition of BMD changes and strategies to optimize bone health are essential. Cancer 2018;124:1025‐35 . © 2017 American Cancer Society . Abstract : Bone mineral density (BMD) decreases with acute lymphoblastic leukemia therapy, especially in patients who are older, have higher BMD Z‐scores at diagnosis, and have greater dexamethasone exposure; and BMD remains low after therapy in patients who have low BMD Z‐scores at diagnosis. In this genome‐wide association study, single‐nucleotide polymorphisms in 2 genes ( COL11A1 and NELL1 ) that play important roles in osteogenesis are associated with a decrease in BMD from diagnosis to week 120.